ANALISIS PERAN DINAS PARIWISATA KOTA PALEMBANG DALAM PENGEMBANGAN WISATA MICE - Anggraini, Meisya; Iqbal, Muhammad; Pratama, Handika Fikri (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
The MICE (Meeting, Incentive, Convention, and Exhibition) industry contributes significantly to economic growth at both national and regional levels. As a metropolitan city in western Indonesia, Palembang holds great potential for MICE tourism development, supported by adequate infrastructure, rich cultural heritage, and an increasing number of events and tourist visits. This study aims to analyze the role of the Palembang City Tourism Office in MICE tourism development, specifically in its functions as a motivator, facilitator, and dynamizer. The study using a descriptive qualitative approach, using in-depth interviews with selected internal informants. The findings show the Palembang City Tourism Office has actively promoted awareness and public participation, established regulations, improved infrastructure, and provided human resource training. It also fosters collaboration among stakeholders and initiates major MICE events. These efforts highlight the government's strategic role in strengthening Palembang’s position as an emerging MICE destination. Keywords: MICE, Role of the government, Motivator, Facilitator, Dynamizer